Investigação genética de casos de deficiência intelectual em populações consanguíneas do sertão paraibano - Cunha, Thalita Cristina Figueiredo (2015)
A part of the populations in Northeastern Brazil are relatively isolated geographically and these populations maintain the tradition of consanguineous marriages for generations. These two factors (isolation and inbreeding) increase the risk of birth of people with autosomal recessive intellectual disabilities. The objective of this study was to determine the genetic causes of intellectual disabilities in two large consanguineous families of Paraiba backlands. In 2012, we conducted an epidemiological study to investigate the contribution of genetic factors in determining the deficiencies in six municipalities of Paraíba previously selected by presenting high consanguinity rate. Families who had patients with neurodegenerative disorders and/or intellectual disabilities (ID) were invited by community health agents for a first screening realized by biologists in order to select patients with deficiency probably caused by genetic mutations. In total, 276 patients were screened, of which, 109 were selected for medical evaluation with neurologists. After medical evaluation, two families with multiple affected individuals in two different forms of autosomal recessive intellectual disability were selected for clinical and genetic research. We performed the linkage study using SNPs array analysis to determine homozygous regions. Subsequently, the whole exome sequencing (WES) of one affected individual of each family was sequenciated. Potentially deleterious variants detected in regions of homozigosity-by descent which were not present in Brazilian population controls or in exomes of global online databases were subject to further scrutiny and segregation analysis by Sanger sequencing. Family A has seven adult siblings with syndromic ID. Phenotype includes tall forehead, prognatism, prominent chin, very large and overhanging nose tip. Homozigosity-by-descent analysis found a 4.0 Mb region in 19q13.32-q13.33 (lod score: 3.24). WES disclosed a homozygous variant (c.418C>T, p.Arg140Trp) in mediator complex subunit 25 (MED25), predicted as deleterious by Provean, Mutation Taster, PolyPhen-2 and SIFT. MED25 is a component of the Mediator complex, involved in regulation of transcription of nearly all RNA polymerase II-dependent genes. Deleterious mutations in MED12, MED17, MED23 and recently after our publication another mutation in the MED25 have been associated with ID. Family B has nine affected adults descending from four closely related first-cousin couples affected by severe non-syndromic ID. Homozigosity-by-descent analysis disclosed a 20.7 Mb region in 8q12.3-q21.2 (lod score: 3.11). WES identified a homozygous deleterious variant in inositol monophosphatase1 gene (IMPA1), consisting of a 5 bp duplication (c.489_493dupGGGCT) leading to frameshift (p.Ser165Trpfs*10). IMPA1 gene product is responsible for the final step of biotransformation of inositol triphosphate and diacylglycerol, two second messengers, and up to now, despite its many physiological functions, no clinical phenotype has been assigned to this gene dysfunction. From this study, it was possible to develop diagnostic test by restriction enzyme and therapeutic perspective for cases associated with IMPA1.